Pengaruh User-Generated Content dan Fenomena ‘Tiktok Made Me Buy It’ Terhadap Keputusan Pembelian Generasi Z: Sebuah Tinjauan Literatur Sistematis - Jilan Azzahra Salsabila; Adiatma Zefanya Loppies; I Made Suparta; Ida Bagus Campena (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to analyze the influence of User Generated Content (UGC) and the ‘TikTok Made Me Buy It’ phenomenon on purchase decisions among Generation Z. The research employs a Systematic Literature Review (SLR) method following the PRISMA guidelines. The data used are secondary data in the form of scientific journal articles obtained from Google Scholar, ScienceDirect, ResearchGate, and SINTA databases within the 2020–2026 period. Based on the selection process, 11 relevant articles that met the inclusion criteria were analyzed. The findings indicate that User Generated Content (UGC) has a positive and significant influence on purchase intention and purchase decisions due to its authenticity and its ability to enhance consumer trust. Furthermore, the ‘TikTok Made Me Buy It’ phenomenon, which includes content virality and electronic word of mouth (e-WOM), plays a significant role in driving consumer behavior through emotional, social, and algorithmic factors. Simultaneously, UGC and e-WOM complement each other in influencing purchase decisions. Generation Z, as active social media users, strengthens these relationships due to their responsiveness to authentic and interactive digital content. This study also identifies a research gap, as most previous studies have focused on purchase intention rather than actual purchase decisions. Therefore, this research contributes to expanding the understanding of consumer behavior in the era of social commerce, particularly on the TikTok platform.